A Different Approach for the Correction of Lower Anterior Crowding - Mete Özer; Ali Bahadır Hor; Selim Arıcı (Galenos Yayinevi, 2005)
In orthodontics, the relapse of mandibular anterior crowding following retention phase is a frequently observed problem. Applying a .018 inch NiTi arch wire from lingual side of lower inter-canine area for realigning of lower incisors is a new kind of treatment in orthodontic practice. A .018 inch NiTi arc wire is chosen and adapted to the inter-canine segment of the lower study model of the patient taken at the end of active orthodontic treatment. In clinic, this wire is firstly bonded to the right or left canine of the patient by using a light-cured composite resin. Then, the NiTi arch wire parts passes far away from the lingual surfaces of the lower incisors at the broken contact points are ligated to these incisors by using .010 inch diameter ligature wire through the embrasures. Finally, the free end of the .018 inch NiTi arc wire is bonded to the other canine. The loosen ligatures due to the incisor movements are tightened at the four week control appointments. This approach could be accepted as a useful clinical application because of its features such as being easy, cheap and time saving, solving the crowding effectively, and it's usage as a permanent retainer after retreatment.